Comparison of GLP-1RAs vs Other Pharmacotherapy for Obesity: A Clinical Review - Overholser, Andrew; Czech, Eric; Speer, Linda; Wilson, Joel; Overholser, Alex (Translation: The University of Toledo Journal of Medical Sciences, 2025)
Background: The Centers for Disease Control and Prevention (CDC) reports that 42% of adults in the United States (US) are obese, and 10% are severely obese. Obesity has many known associated health risks, and successful treatment decreases those risks. Management always includes diet and lifestyle changes and drug therapy can improve weight loss. The current United States Food and Drug Administration (FDA) approved pharmaceutical therapy choices for long-term use include a combination of phentermine-topiramate, combination bupropion-naltrexone, orlistat, glucagon-like peptide-1 receptor agonists (GLP-1RAs), and dual action GLP-1RAs and gastric inhibitory peptide agonists (GIP). Objectives: This review will summarize evidence comparing the safety and efficacy of GLP-1RAs or GLP-1RAs/GIP agonists with other pharmacologic treatments to achieve and maintain weight loss, improve quality of life, and reduce morbidity in obese adults. Methods: We completed a literature review of multiple databases, including PubMed, Embase, Google Scholar, and Cochrane databases, to identify studies about pharmacologic treatment for overweight or obese adults with or without T2DM and reporting outcomes of mean percentage body weight loss. An emphasis was placed on choosing meta-analyses and primary studies in patients without T2DM. We excluded articles older than 5 years or published in a language other than English. 19 meta-analyses and 2 randomized controlled trials (RCTs) were chosen, and 13 meta-analyses were excluded based on not meeting the inclusion criteria. 6 meta-analyses and 2 RCTs were included. Results: The literature showed that over 52 weeks, liraglutide reduced mean body weight percentage by 4.81% (95% CI: 4.23%-5.39%). Between a 12-68 week period in patients receiving semaglutide, three meta-analyses reported reduced weight by 12.57% [97% CI 10.35%-14.80%,) 10.55% (95% CI 6.96%-14.13%,) and 10.09% (95% CI: 8.33%-11.84%.) Tirzepatide, a novel GLP-1RA and GIP agonist, recently completed a phase-3 RCT, which showed that over 72 weeks, the mean weight percentage decrease was 18.4% (95% CI: 18.5%-23.2%) vs a 3.1% weight gain with placebo, a change of 21.8%. Each of the GLP-1RA agents (including tirzepatide) improved cardiometabolic risk factors. Phentermine-topiramate reduced mean body weight percentage by 8.45% (95% CI, 7.89%–9.01%) after 52-56 weeks. Bupropion-naltrexone reduced mean body weight percentage by 3.01% (95% CI, 2.47%–3.54%) over 56 weeks. Finally, orlistat reduced mean body weight percentage by 2.78% (95% CI, 2.36%–3.20%) after 1-4 years. Semaglutide is a well-established drug with weight loss, but tirzepatide shows the most promise in being the superior agent. Conclusion: It is well known that pharmacotherapy with diet and exercise is more effective than diet and exercise alone in achieving weight loss. The GLP-1RAs are effective for weight loss, with semaglutide more effective than phentermine-topiramate, bupropion-naltrexone, orlistat, and liraglutide. Tirzepatide shows promise as a superior agent, but more comprehensive studies need to be done. When choosing pharmacotherapy, utilizing a GLP-1RA (semaglutide) or a dual GLP-1RA/GIP agonist (tirzepatide) can improve cardiometabolic risk factors and quality of life and is more effective than any other FDA-approved agent. ?